The interaction of asbestos and iron in lung tissue revealed by synchrotron-based scanning X-ray microscopy - Pascolo, Lorella (Nature Publishing Group, 2013)
Asbestos is a potent carcinogen associated with malignant mesothelioma and lung cancer but its carcinogenic mechanisms are still poorly understood. Asbestos toxicity is ascribed to its particular physico-chemical characteristics, and one of them is the presence of and ability to adsorb iron, which may cause an alteration of iron homeostasis in the tissue. This observational study reports a combination of advanced synchrotron-based X-ray imaging and micro-spectroscopic methods that provide correlative morphological and chemical information for shedding light on iron mobilization features during asbestos permanence in lung tissue. The results show that the processes responsible for the unusual distribution of iron at different stages of interaction with the fibres also involve calcium, phosphorus and magnesium. It has been confirmed that the dominant iron form present in asbestos bodies is ferritin, while the concurrent presence of haematite suggests alteration of iron chemistry during asbestos body permanence.